Pengaruh Orientasi Gaya Kepemimpinan Terhadap Disiplin Kerja Pegawai di Badan Kepegawaian Daerah Kota Bandung - Gina Sugina; Asep Suryana; Eka Prihatin (Universitas Pendidikan Indonesia, 2019)
This study entitled “The Influence of Leadership Style to Employee’s Discipline in Bandung Staffing Berau (Badan Kepegawaian Daerah (BKD) Kota Bandung)”. The research questions of this study is about employee’s discipline who work in Bandung Staffing Berau. The aims of this study is obtain the actual picture of the influence of the orientation of leadership style on employee’s discipline in BKD Kota Bandung. The method used in this research is descriptive method with a quantitative approach. While the data collection techniques used through thequestionnaire enclosed with a four rating scale (Likert). Population is used as a source of data in this research study as well as the sample is the entireemployee BKD Kota Bandung by 94 employees. Based on the results of data processing computed by using the WMS (Weight Means Scored) showed that the average general tendency for the variable X (Orientation Leadership Style) of 3.13 and be in the good category, and the general trend of the average for the variable Y (Employee’s Discipline ) of 3.21 to be in good category. Results of testing normality of data distribution, it is known that the variables X and Y variables are normally distributed. Judging from the calculation of the correlation coefficient of 0.625 which shows that there is a strong relationship between variables X and variable Y, while the calculation of significant test of 7.680 proved significant. The results of the analysis of the determination coefficient of 39.06% shows the influence of the influence of leadership style to employee’s discipline is at 39.06% and the rest of them are influenced by other factors. The regression equation ̅ means each one unit increase of leadershipstyle variable provides the increase of employee’s discipline as much as 0.625 unit. This study conclusion states leadership style effects significantly toemployee’s discipline in BKD Kota Bandung.